Perceptions and Experiences of Intimate Partner Violence in Abidjan, Côte d'Ivoire. - Shuman, Sara J; Falb, Kathryn L; Cardoso, Lauren F; Cole, Heather; Kpebo, Denise; Gupta, Jhumka (PloS one, 2016)
Men and women's perceptions of intimate partner violence (IPV) within crisis-affected populations are not well understood. This mixed-methods study examined the frequency of IPV against women in urban Cote d'Ivoire, and qualitatively explored how men and women perceive the impact of various forms of IPV on health, everyday activities, and feelings of shame.